Decentralization in Educational Disparity of the Southeast Sulawesi Province - Obed Bida (Policy & Governance Review, 2018)
Educational disparity is a public issue that continues to be an endless subject matter of discourse due to the highly centralistic process of education policy in the government bureaucracy. This research aims to understand the pattern of educational disparity occurring in the islands of Southeast Sulawesi Province, Indonesia. The role of political actors in the success of education policy is a vital element in the policy process, and this is apparent in the significance of the political aspect in the education policy process, which emphasizes more on political approaches rather than actual social, economic, and geographical conditions. This study was conducted using the descriptive qualitative approach with data collection techniques that included observations, in-depth interviews, and document analysis in Buton and South Buton Regencies. Study results indicate that the education policy pattern developing in island regions is inclined to using the spatial approach with a central area priority scale, and the structural elite approach, which is political lobbying employed by structural elites (school principals) targeting education bureaucracy in the region. The education policy pattern developing in the region actually has an impact on educational disparity in the public, both at the district and regency levels. In general, the education decentralization policy has yet to run optimally on account of educational resources in the region being distributed by using the spatial and structural elite approaches which have, consequently, created a pathological behavior in the education bureaucracy that is chockfull of vested interests.